SISTEM INFORMASI BANK SAMPAH PADA BANK SAMPAH INDUK CAHAYA KENCANA MANIS KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Rozaq, Abdul; Krisna Ade Satria, Maximilianus; Yuniar Fahmi, Rizka; Fitri, Rahimi (P3M Politeknik Negeri Banjarmasin, 2025)
Garbage is an environmental problem that is very complex and complicated to solve. The presence of waste banks is an alternative to reduce waste problems by converting waste into rupiah. The research was conducted with the aim of designing and developing an information system that can be applied to the Parent Waste Bank Cahaya Kencana Manis Banjar Regency, South Kalimantan Province in order to provide optimal information and can be accessed in real time by its customers. This type of research uses the Research and Development (R&D) research method and the waterfall method as a development method applied to the waste bank information system to ensure that the resulting information system meets user needs by applying communication, planning, modeling, construction, and deployment. The design results are converted into a system that runs according to business flow with the Bootstrap framework and MySQL database. As a result, the waste bank information system was successfully created and implemented at the Parent Waste Bank Cahaya Kencana Manis Banjar Regency, South Kalimantan Province. The information system also supports a responsive display when accessed using a mobile device. Blackbox testing results show that the information system can run as needed